2015
DOI: 10.1080/17457300.2015.1061562
|View full text |Cite
|
Sign up to set email alerts
|

A prospective registry evaluating the epidemiology and clinical care of traumatic brain injury patients presenting to a regional referral hospital in Moshi, Tanzania: challenges and the way forward

Abstract: Traumatic brain injury (TBI) is the most common cause of death and disability globally disproportionately affecting low- and middle-income countries where increasing injury rates are compounded by limited quality care. The objective of this study is to describe quality of care for TBI patients who presented to Kilimanjaro Christian Medical Center, Moshi, Tanzania. We evaluated a prospective quality improvement TBI registry that enrolled consecutive patients with acute TBI. Descriptive statistics and qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 28 publications
3
99
1
Order By: Relevance
“…Only 35% of all RTIs from this police data set were associated with motorcycle use. This is somewhat lower than local hospital-based data which demonstrates that 49% of road traffic crash victims who present for care of a traumatic brain injury were on a motorcycle 17 . This discrepancy may be due to underreporting of RTIs involving motorcycles, as motorcycle crashes have been shown to be subject to underreporting bias 28,29 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Only 35% of all RTIs from this police data set were associated with motorcycle use. This is somewhat lower than local hospital-based data which demonstrates that 49% of road traffic crash victims who present for care of a traumatic brain injury were on a motorcycle 17 . This discrepancy may be due to underreporting of RTIs involving motorcycles, as motorcycle crashes have been shown to be subject to underreporting bias 28,29 .…”
Section: Discussionmentioning
confidence: 62%
“…This increase in road traffic has presumably led to an increase in RTCs and RTIs. In one recent study, approximately two-thirds of traumatic brain injuries presenting for care at the local hospital were from RTIs 17 . In order to design effective strategies to reduce morbidity and mortality from RTIs in cities like Moshi across the developing world, more data is needed regarding regional epidemiology, underlying causative factors, and socioeconomic burdens of RTCs in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…In Moshi, Tanzania, a smaller city than Mwanza, among prospectively enrolled severe TBI patients the mortality was 47.0%, however, there is no trained neurosurgeon at Moshi. 27 In a retrospective chart study from Uganda, the mortality was 25.8%. 28 The 2-week mortality in the recent BEST-TRIP trial conducted in South America was 21–30% and at 6-months 40% in severe TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…(Michaels et al, 2000) In the sam e study, 42% of patients reported symptoms suffering from a severe TBI (GCS < 9) and 75% from a mild TBI (GCS > 13 (Staton et al, 2017).…”
Section: Mental Healthmentioning
confidence: 99%
“…Injuries like severe burns can suffering from a severe TBI (GCS < 9) and 75% from a mild TBI (GCS > 13 (Staton et al, 2017).…”
Section: Painmentioning
confidence: 99%